Immunological Endotyping of Chronic Critical Illness After Severe Sepsis - Fenner, Brittany P.; Darden, D. B.; Kelly, Lauren S.; Rincon, Jaimar; Brakenridge, Scott C.; Larson, Shawn D.; Moore, Frederick A.; Efron, Philip A.; Moldawer, Lyle L. (Frontiers in Medicine, 2021)
Improved management of severe sepsis has been one of the major health care accomplishments of the last two decades. Due to enhanced recognition and improved management of severe sepsis, in-hospital mortality has been reduced by up to 40%. With that good news, a new syndrome has unfortunately replaced in-hospital multi-organ failure and death. This syndrome of chronic critical illness (CCI) includes sepsis patients who survive the early ‘cytokine or genomic storm’, but fail to fully recover, and progress into a persistent state of manageable organ injury requiring prolonged intensive care. These patients are commonly discharged to long-term care facilities where sepsis recidivism is high. As many as 40% of sepsis survivors develop CCI. CCI is the result, at least in part, of a maladaptive host response to chronic pattern-recognition receptor (PRR)-mediated processes. This maladaptive response results in dysregulated myelopoiesis, chronic inflammation, T-cell atrophy, T-cell exhaustion, and the expansion of suppressor cell functions. We have defined this panoply of host responses as a persistent inflammatory, immune suppressive and protein catabolic syndrome (PICS). Why is this important? We propose that PICS in sepsis survivors is its own common, unique immunological endotype driven by the constant release of organ injury-associated, endogenous alarmins, and microbial products from secondary infections. Despite being a common outcome, there are no therapeutic interventions other than supportive therapies for this common disorder. Only through a complete understanding of the immunological endotype of PICS can rational therapeutic interventions be designed.